Кінематографічна колористика пленеру в малій прозі Володимира Дрозда 1960-х років - Брайко, О. (Слово і Час, 2020)
У статті проаналізовано стильову манеру ранньої прози В. Дрозда з
погляду кінематографічної естетики кольору й можливостей екранного моделювання пленеру як найбільш вільного просторового середовища
для візуальної репрезентації образної думки. У порівняльному аспекті
запропоновано й розглянуто аналоги до мистецьких знахідок українського письменника у відомих фільмах («Жовтень», «Поема про
море», «Червона пустеля»). The paper considers the style manner of V. Drozd’s prose from his early writing period with
a focus on cinematographic aesthetics of color and possibilities of the screen design of plein
air as the most free spatial environment for visual development of the image. The writer’s literary
means have their analogues in the well-known contemporary films (“October”, “Poem
about Sea”, “Red Desert”).
The dynamic plein air compositions have certain screen potential. The images of openspace
are related to freedom in dynamic and successive change of a scene, and alternation of
verbal pictures. They are rather close to the specific cinematographic representation of action,
as their color markers may be associated with an imaginary film. The first V. Drozd’s attempts
of designing the color and light of plein air are marked with an accent on the hues of the
represented objects, the dynamism of objects in the imaginary shots, and expressive motion,
increased with spectral indicators. A growth of the writer’s mastery is related to development
of successive color ‘melody’, based on nuances of the visual impressions, and harmonized with
internal action progress. Plastic imaginal markers with limited color range also remind the
technique of cinematographic rush, adding emotional and psychological mood connotations
to the narration and stimulating positive (nostalgic, elegiac) associations. Although they may
seem random, the light and color signals acquire cinematographic expressiveness due to integration
into the plot and its internal action, and to the dynamics of the character’s point of
view. Abandoning a picturesque fixed nature, the author acquires possibility to decode wider
associative meanings with color and light markers, search for deeper semantics of visual image
complexes, and construct deterministic relations of a character and environment. Even minimal
visual signals contribute to the color structure of a verbal shot. Such terseness and obscurity
of objects in the prospect of a narrative camera, and a rapid change of plein air sections are
similar to the features of cinematographic aesthetics and poetics.